2022
DOI: 10.3389/fcell.2022.832348
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic CpG Islands and Their Impact on Gene Regulation

Abstract: The mammalian genome is depleted in CG dinucleotides, except at protected regions where they cluster as CpG islands (CGIs). CGIs are gene regulatory hubs and serve as transcription initiation sites and are as expected, associated with gene promoters. Advances in genomic annotations demonstrate that a quarter of CGIs are found within genes. Such intragenic regions are repressive environments, so it is surprising that CGIs reside here and even more surprising that some resist repression and are transcriptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…CGi are often localized in genes’ promoters and usually not methylated. Conversely, CGi associated with intra- or inter-genic regions can be methylated or not methylated [ 31 , 32 ]. This leads to a heterogeneous epigenetic landscape.…”
Section: Resultsmentioning
confidence: 99%
“…CGi are often localized in genes’ promoters and usually not methylated. Conversely, CGi associated with intra- or inter-genic regions can be methylated or not methylated [ 31 , 32 ]. This leads to a heterogeneous epigenetic landscape.…”
Section: Resultsmentioning
confidence: 99%
“…Hypermethylation of gene-body CpGs can induce activation of transcription, yet the role of intragenic CpG islands is more complex and not fully understood. These regions, if hypermethylated can also inhibit gene transcription and have functions similar to promotor or enhancer regions [ 46 ]. Downstream analysis of AHRR function showed no impact on cell proliferation, rather proteomic studies revealed upregulation of proteins associated with epithelial-mesenchymal transition following AHRR KD.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach was downregulated genes with CGIs but is important to announce that DNMT3B overexpression also was related to the up-regulation of several genes. The methylation in intragenic CGIs 51 is related to cell differentiation 52 , 95 , active transcription, and enrichment of histone modifications such as H3K36me3 50 . We studied genes possibly related to the catalytic DNMT3B function, and a limitation of our study is that we can’t discriminate whether the change observed in all the deregulated genes is a catalytic or accessory function of DNMT3B 96 , we specifically tested the catalytic function in the 4 selected genes.…”
Section: Discussionmentioning
confidence: 99%